Viewpoint: Rigorous monitoring is necessary to guide food system transformation in the countdown to the 2030 global goals. (October 2021) - Fanzo, Jessica; Haddad, Lawrence; Schneider, Kate R.; Béné, Christophe; Covic, Namukolo M.; Guarin, Alejandro; Herforth, Anna W.; Herrero, Mario; Sumaila, U. Rashid; Aburto, Nancy J.; Amuyunzu-Nyamongo, Mary; Barquera, Simon; et al.
Highlights: Food system transformation is urgent, requiring rigorous, science-based monitoring to guide public and private decisions and support those who hold decision-makers to account. Monitoring the whole of food systems and the interactions between their components is essential to support the immediate course corrections required to meet global sustainable development goals. A food systems framework is proposed to define the architecture for a comprehensive monitoring agenda covering five thematic areas and their component indicator domains. An inclusive process is called for that would select and track indicators for analysis of food systems performance and accountability. Abstract: Food systems that support healthy diets in sustainable, resilient, just, and equitable ways can engender progress in eradicating poverty and malnutrition; protecting human rights; and restoring natural resources. Food system activities have contributed to great gains for humanity but have also led to significant challenges, including hunger, poor diet quality, inequity, and threats to nature. While it is recognized that food systems are central to multiple global commitments and goals, including the Sustainable Development Goals, current trajectories are not aligned to meet these objectives. As mounting crises further stress food systems, the consequences of inaction are clear. The goal of food system transformation is to generate a future where all people have access to healthy diets, which are produced in sustainable and resilient ways that restore nature and deliver just, equitable livelihoods. A rigorous, science-based monitoring framework can support evidence-based policymaking and the work of those who hold key actors accountable in this transformation process. Monitoring can illustrate current performance, facilitate comparisons across geographies and over time, and track progress. We propose a framework centered around five thematic areas related to (1) diets, nutrition, and health; (2) environment and climate; and (3) livelihoods, poverty, and equity; (4) governance; and (5) resilience and sustainability. We hope to call attention to the need to monitor food systems globally to inform decisions and support accountability for better governance of food systems as part of the transformation process. Transformation is possible in the next decade, but rigorous evidence is needed in the countdown to the 2030 SDG global goals.